Stability, Asymptotic and Exponential Stability for Various Types of Equations with Discontinuous Solutions Via Lyapunov Functionals - Gallegos-Castro, C (Academic Press, 2021)
In this paper, we are interested in investigating stability results for generalized ordinary differential equations (generalized ODEs in short), and their applications to measure differential equations and dynamic equations on time scales. First, we establish stability, asymptotic and exponential stability for the trivial solution of generalized ODEs. Secondly, we use the well known correspondence between solutions of generalized ODEs and solutions of measure differential equations, obtaining analogues results for the last equations. Finally, we apply some of these results for dynamic equations on time scales. © 2021 Elsevier Inc.